THU0279 POLYUNSATURATED FATTY ACIDS (PUFAS) AND SPECIALIZED PRO-RESOLVING MEDIATORS (SPMS) ARE DECREASED IN PLASMA AND SERUM FROM SLE PATIENTS COMPARED TO HEALTHY CONTROLS. (June 2019) - Davis-Porada, Julia; Serhan, Charles; Norris, Paul; Lipsky, Peter; Salmon, Jane E.
Abstract : Background: Systemic lupus erythematosus (SLE) is an autoimmune disease with persistent, inflammatory mediated organ damage. It has been suggested that omega-3-polyunsaturated fatty acids (PUFAs) are low in SLE patients and that supplementation with omega-3 PUFAs might be beneficial. Omega-3 PUFAs can be metabolized to specialized pro-resolving mediators (SPM) in inflamed tissues. PUFAs, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), give rise to protectins and E-series and D-series resolvins, respectively. These SPMs help promote tissue repair and healing in addition to reducing neutrophil infiltration. Objectives: To investigate (1) if SMPs can be measured in lupus patient blood and (2) whether EHA and DHA and SPMs were dysregulated in lupus patients compared to controls. Methods: Blood samples were collected from 12 patients enrolled in the Autoimmune Disease Registry and Repository, a single center registry (1996-present) of patients meeting ACR SLE classification criteria. Samples were collected from 12 non-SLE-controls who were age (± 5 years) and race/ethnicity matched. Metabolomic profiling via tandem mass spectrometry (LC-MS-MS) was performed on serum and plasma to assess the PUFA and SPM levels. Results: Levels of EPA and DHA were highly correlated in serum and plasma. Both EPA and DHA were significantly decreased in SLE patients compared to controls (Table 1 ). Neither plasma nor serum DHA or EPA levels was correlated with disease activity assessed by SLEDAI score. SPMs including PD1 and RvE1 as well as their precursors, 17-HDHA and 18-HEPE, were identified in plasma and serum samples from SLE patients. Plasma levels of 17-HDHA, as well as serum levels of PD1, 17-HDHA, and 18-HEPE tended to be reduced in SLE (Table 1 ). The SLE patients with a history of nephritis had significantly lower levels of DHA (p=0.03), EPA (p=0.05), 18-HEPE (p=0.03), and 17-HDHA (p=0.04) than SLE patients without nephritis. Conclusion: SLE patients have lower levels of circulating EPA and DHA, the substrates for SPMs, relative to individuals without SLE. Lower levels of these PUFAs and some SPMs are associated with history of nephritis. Additionally, the levels of PD1, 17-HDHA, and 18-HEPE were measurable in SLE serum and plasma and tended to be reduced, especially in subjects with lupus nephritis. SPMs suppress the production of inflammatory mediators and promote resolution of inflammation. The lower levels of PUFAs and SPMs could contribute to the likelihood of developing lupus nephritis. Further evaluation of this relationship is warranted. Metabolite (in serum) mean, (SD) Control (n=12) SLE (n=12) P Value Disclosure of Interests: Julia Davis-Porada: None declared, Charles Serhan: None declared, Paul Norris: None declared, Peter Lipsky Consultant for: Consulting fees from Horizon Pharma, Jane E. Salmon Shareholder of: Biogen-Idec, BMS, Johnson & Johnson, Regeneron, Merck, Grant/research support from: UCB, Consultant for: BMS, Ionis